Pelatihan Jurnalistik Berbasis Majalah Digital bagi Para Pengurus OSIS di Sekolah - Tias, Dhea Ayuning; Nurhadi, Zikri Fachrul (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Journalism if applied to the world of education will be increasingly relevant. SMP Plus Darul Arham, which was only established in 2020, when viewed from the concept of education, has shortcomings in the form of the absence of communication media such as mading or bulletins which should be a forum for student creativity as well as a means of publication at school. So, journalistic training is recommended in this school with the aim of providing an overview of how the application of journalism with a digital magazine base is carried out. With a journalistic approach consisting of finding information, processing information and then publishing the results of their work, in the process team-based projects are also used with the intention that students are trained to be able to learn and understand the situation of the conditions and the final target that has been given. As a result, students were enthusiastic about the assignment and the final magazine project. Marked by the increase in student initiative in interviews as well as the increase in student creativity when inputting news into the digital magazine rubric that has been provided. In order for students to continue to develop their creativity, the partners are motivated to further equip facilities for this to happen. Other long-term benefits that can be used as suggestions from this training also provide an idea to collaborate with certain subjects so that the school magazine as a bridge of information as well as school promotion can continue to run, which is also in line with the Merdeka curriculum which has a pro-school program.